A hybrid modular multilevel converter with partial embedded energy storage - Konstantinou, Georgios (2018)
Modular and cascaded multilevel converters provide a functional solution for the integration of energy storage systems (ESSs). This paper develops a hybrid multilevel converter based on the modular multilevel converter (MMC) that can be functionally extended with partial embedded ESS as a fraction of the overall converter power rating. The configuration, which can operate as a typical DC-AC converter, enables multi-directional power flow between the DC- and AC-side of the converter, as well as the embedded energy storage elements. The use of a three-phase flying-capacitor submodule eliminates the second-order harmonic oscillations present in modular cascaded multilevel converters. Current, voltage and power control are discussed in the paper while simulation results illustrate the operation of the hybrid MMC as a DC-AC converter in a typical inverter application and the additional functions and control of the embedded ESS.